CHD7 targets active gene enhancer elements to modulate ES cell-specific gene expression. - Michael P Schnetz; Lusy Handoko; Batool Akhtar-Zaidi; Cynthia F Bartels; C Filipe Pereira; Amanda G Fisher; David J Adams; Paul Flicek; Gregory E Crawford; Thomas Laframboise; Paul Tesar; Chia-Lin Wei; et al. (PLoS Genetics)
CHD7 is one of nine members of the chromodomain helicase DNA-binding domain family of ATP-dependent chromatin remodeling enzymes found in mammalian cells. De novo mutation of CHD7 is a major cause of CHARGE syndrome, a genetic condition characterized by multiple congenital anomalies. To gain insights to the function of CHD7, we used the technique of chromatin immunoprecipitation followed by massively parallel DNA sequencing (ChIP-Seq) to map CHD7 sites in mouse ES cells. We identified 10,483 sites on chromatin bound by CHD7 at high confidence. Most of the CHD7 sites show features of gene enhancer elements. Specifically, CHD7 sites are predominantly located distal to transcription start sites, contain high levels of H3K4 mono-methylation, found within open chromatin that is hypersensitive to DNase I digestion, and correlate with ES cell-specific gene expression. Moreover, CHD7 co-localizes with P300, a known enhancer-binding protein and strong predictor of enhancer activity. Correlations with 18 other factors mapped by ChIP-seq in mouse ES cells indicate that CHD7 also co-localizes with ES cell master regulators OCT4, SOX2, and NANOG. Correlations between CHD7 sites and global gene expression profiles obtained from Chd7(+/+), Chd7(+/-), and Chd7(-/-) ES cells indicate that CHD7 functions at enhancers as a transcriptional rheostat to modulate, or fine-tune the expression levels of ES-specific genes. CHD7 can modulate genes in either the positive or negative direction, although negative regulation appears to be the more direct effect of CHD7 binding. These data indicate that enhancer-binding proteins can limit gene expression and are not necessarily co-activators. Although ES cells are not likely to be affected in CHARGE syndrome, we propose that enhancer-mediated gene dysregulation contributes to disease pathogenesis and that the critical CHD7 target genes may be subject to positive or negative regulation.